Stressors and Mental Health of Students at Private University in Malaysia - Othman, Mohd Noor Azman; Rashid, Mas Anom; Ibrahim, Abdul Razak (2017)
The Malaysian Ministry of Health has aired its concern towards the state of Malaysian students’ mental health in the late 2016.Statistics revealed a worsening state of mental health problems among Malaysian students, which shows that there is an increase cases of mental health from 2011 to 2016.Experts cite anxiety and depression as the main causes of mental health problems among students although not ruling out the influence of drugs as a factor.Hence, this study is aimed to seek some answers to the state of the students overall mental health, what are the most influential factor that affects their mental health and how they manage these issues. A total of 350 students participated in this study and findings revealed that 50% of the students suffered some kind of depressions triggered by various factors.